Youth Response to Tasya Farasya as Wardah Cosmetic Promotion Media: Respon Remaja pada Tasya Farasya sebagai Media Promosi Kosmetik Wardah - Devi Selvia Ramadhanni; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to investigate the adolescent reception of beauty vlogger Tasya Farasya as a promotional medium for Wardah cosmetic brand through her YouTube video titled